Deletion, insertion and stop codon mutations in vif genes of HIV-1 infecting slow progressor patients - Héctor Rafael Rangel; Domingo Garzaro; Anny Karely Rodríguez; Alvaro Hernán Ramírez; Gladys Ameli; Cristina del Rosario Gutiérrez; Flor Helene Pujol (Journal of Infection in Developing Countries)
Background: Variable progression towards AIDS has been described and has been related to viral and host factors. Around 10% of the HIV-1 infected patients are slow progressors (SP), not presenting with AIDS disease signs even after more than 10 years of infection. Viral gene defects have been associated with the disease progression but more studies are still needed. Methodology: The sequence of vif and nef were analyzed for HIV-1 infecting 14 SP and 46 normal progressors (NP) patients. Results: Co-circulation of a strain carrying vif deleted gene with the wild type strain was detected in an SP patient with more than 10 years of infection. Other mutations (insertion in aa 63 in one strain, two premature stop codons in another one) were found in viruses infecting two other patients. Except for the SP8 strain, which exhibited a premature stop codon in nef, no gross deletions or insertions were observed in nef genes of both NPs and SPs strains analyzed. Conclusions: Different kind of mutation: deletion, insertion and stop codon, were detected in 3/14 samples from SP, with co-circulation of a 195 bp vif deletion virus with a wild type in one of these patients. Although vif defects do not seem to be a frequent feature in SPs, this study illustrates the importance of analysing this gene, in addition to the multiple factors associated with the long-term non progression to AIDS.